STUDENT SATISFACTION ON BOARDING SCHOOL (PESANTREN) FACILITIES AND INFRASTRUCTURE FOR EDUCATION - Lismawati; Subiyantoro; Lili Nur Amaliyah (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2023)
The management of infrastructure which is often neglected has an impact on the success of educational programs in schools. Therefore, fulfilling the needs and optimizing the infrastructure is very much needed. The purpose of this study was to determine the use of Islamic boarding schools' educational facilities and infrastructure in Bener Meriah district, Aceh, Indonesia. The approach used in this study is an explorative qualitative approach. data collection methods using interview techniques, observation, and documentation. The results of the study show that the educational facilities and infrastructure of Islamic boarding schools in Bener Meriah district, Aceh have optimized their utilization in supporting the development of human resources. But there are the obstacles found in Islamic boarding schools in Bener Meriah district, Aceh, namely: 1) there are still facilities and infrastructure that have not been updated by the school such as libraries, 2) school buildings that are not suitable for areas where rainfall is more frequent, so that sometimes it causes flooding. Based on this research, it is recommended to pay maximum attention to the condition of infrastructure and be quick in repairing infrastructure that is no longer feasible, empowering human resources according to needs through infrastructure to improve the quality of education towards superior and competitive human resources starting from the quality of educator performance professional.